2014
DOI: 10.1088/0004-637x/793/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Alma Observations of Infalling Flows Toward the Keplerian Disk Around the Class I Protostar L1489 Irs

Abstract: We have conducted ALMA observations in the 1.3 mm continuum and 12 CO (2-1), C 18 O (2-1) and SO (5 6 -4 5 ) lines toward L1489 IRS, a Class I protostar surrounded by a Keplerian disk and an infalling envelope. The Keplerian disk is clearly identified in the 12 CO and C 18 O emission, and its outer radius (∼700 AU) and mass (∼0.005 M ⊙ ) are comparable to those of disks around T Tauri stars. The protostellar mass is estimated to be 1.6 M ⊙ with the inclination angle of 66 • . In addition to the Keplerian disk,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
138
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 129 publications
(172 citation statements)
references
References 86 publications
30
138
4
Order By: Relevance
“…The formation of Keplerian disks is closely related to the dynamical transition from the infall motion in protostellar envelopes to the Keplerian rotation. In fact, such a transition is being observationally revealed around several protostars by the most recent studies Chou et al 2014;Ohashi et al 2014;Takakuwa et al 2014;Yen et al 2014). The number of samples is, however, still too limited to perform any statistical study.…”
Section: Introductionmentioning
confidence: 98%
“…The formation of Keplerian disks is closely related to the dynamical transition from the infall motion in protostellar envelopes to the Keplerian rotation. In fact, such a transition is being observationally revealed around several protostars by the most recent studies Chou et al 2014;Ohashi et al 2014;Takakuwa et al 2014;Yen et al 2014). The number of samples is, however, still too limited to perform any statistical study.…”
Section: Introductionmentioning
confidence: 98%
“…As discussed by Takakuwa et al (2013), in the case of L1551 NE the magnetic braking may be efficient in the envelope region but inefficient in the disk due to the higher plasma β, the ratio of the gas thermal pressure to the magnetic pressure. Around a Class I protostar L1489 IRS, Yen et al (2014) have identified free-falling gas with the rotational angular momentum consistent with that of the outer boundary of the Keplerian disk. In the case of L1489 IRS the amount of the surrounding envelope is much smaller (∼0.02 M ) than that of L1551 IRS 5 and L1551 NE, and thus the free-falling gas component may be a remnant gas component falling toward the central disk.…”
Section: Keplerian Disk Embedded In the Infalling Envelope Around L15mentioning
confidence: 96%
“…Three-dimensional structure is clearly required rather than a planar disk-like system, given the nearly face-on geometry. Alternatively, such a non-axisymmetric structure evokes the infall streams found in several low-mass protostars and protobinaries (e.g., Mayama et al 2010;Casassus et al 2013;Tang et al 2014;Yen et al 2014). In particular, recent ALMA observations toward a low-mass class 0 object have found that similar non-axisymmetric streams fall down onto the edge-on accretion disk along a parabolic orbit (Yen et al 2014).…”
Section: Origin Of the Velocity Gradientmentioning
confidence: 99%